PROVISION OF PUBLIC PRACTICES IN THE DIGITAL AGE GOVERNMENT - Abdul Halil Hi. Ibrahim; Iksan R.A. Arsad; Rasid Pora (Adisam Publisher, 2024)
The digital age has brought significant changes to the global social, economic, and political order, deeply affecting the structure and functioning of public policy. The study aims to dig into the dynamics of public policy in the digital age of governance, assessing the approaches, influences, and implications of such transformations on the maintenance of government and public service. By adopting methods of literary research, the study provides in-depth analysis of how digital technology has been used to improve efficiency, transparency, and participation in public policy processes, as well as identifying emerging challenges and opportunities. The results of this study show that governments in various parts of the world have undertaken a number of initiatives to incorporate digital technology into their public policy strategies, resulting in significant improvements in terms of service access, service quality, and public participation and engagement. However, challenges such as digital gaps, cybersecurity, and personal data protection need to be overcome to maximize the benefits of public policy in the digital age.